IDENTIFIKASI RHODAMIN B DALAM SAUS SAMBAL YANG BEREDAR DI KOTA PEKALONGAN - Siska Rusmalina; Metha Anung Anindhita (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2015)
Rhodamine B is prohibited additive used on foods. If these compound into the body, can lead  to  damage  to  the  liver,  kidney,  spleen  and  anatomical  changes  in  organs.  However,  this compound is found in many foods that are red as chili sauce. To protect the public from abuse of  these  compounds,  the  study  of  Rhodamine  B  in  chili  sauce  sold  in  the  traditional  market needs to be done. This research is descriptive qualitative. The location was used in this study is mains three traditional markets in the city of Pekalongan with a total of samples chilli sauce is eight.  Rhodamine  B  in  chili  sauce  detected  by  linking  the  coumpoud  on  the  wool  yarn,  then washed  with    water  flowing.  Chili  sause  samples  tasted  positive  for  Rhodamine  B,  if  the analyte bound to the wool yarn can not be leached by water flowing. The result of this research was eight samples of the chili sauce does not contain dye Rhodamine B. As evidenced by the color of analyte Rhodamine B on wool yarn can be washed by water.